A Cultural Dimension in Language Education. A Comparative Study in Culture Teaching Between a TCF and TFF Class - Xu, Liang (My University, 2007)
Traditionally, the teaching of culture has been neglected or narrowed to the teaching of culture knowledge as contents in a textbook. Today, the focus is not only on the teaching of culture within the textbook, but also through intercultural communication. Many foreign language teaching experts have empathetically argued that language and culture should not be regarded as isolated sections. Instead, the teaching of culture should be completely and appropriately integrated in the foreign language class. The present study aims to examine foreign language teachers’ views on what culture is and how it should be taught. Special emphasis is placed on the factors that interfere with the teaching of culture, namely the textbook and intercultural communicative competence (ICC). The definition of culture and its relationship with language in the language education is analyzed. The concept of intercultural communicative competence is also discussed. As a teaching objective, it is expected to embrace cultural knowledge, awareness and skills. A comparative research between the Teaching Chinese to Foreigners (TCF) and Teaching Finnish to Foreigners (TFF) was designed and is discussed generally from two perspectives of culture teaching, namely textbooks and ICC teaching practice. This comparison was conducted through textbook contents analysis and questionnaires with Liker-scale and open-ended questions, by means of which data was collected from teachers and students from these two classes. The result of the study suggests that the teaching of culture has been viewed as an objective of importance. However, teachers seem hesitant to go beyond the traditional approach of language and culture teaching. There are some practical barriers that hamper ICC, as an objective, from gaining its own right place in the language class.
Keywords: culture teaching; language; Intercultural Communicative Competence; textbook; fi=Englannin kieli|en=English language|